Comida de casa, comida da escola: as contribuições do PNAE na preservação dos hábitos alimentares em Coruripe, Alagoas - Santos, Rafaela dos (2019)
Territorialities, such as practices of social reproduction and eating habits, are based on cultural identities and form material and symbolic elements that increase territories. Over the centuries, technological innovations have expanded the range of food production and reach, adding to the succession of cultural exchanges driven by the communication and transportation networks, have enabled the establishment of food empires as well as the spread of industrialized foods. Yet, these reconfigurations of production and consumption have not decimated problems such as hunger, malnutrition and other health, social and environmental problems related to to current food. In 1948, the Declaration of Human Rights was prepared, a document that, for the first time, established adequate food as a human right. In Brazil, the theme is the focus of other normative instruments, such as the National School Feeding Policy (PNAE). This public policy is linked to the National Fund for the Development of Education, which transfers financial resources to purchase food for the country's public and philanthropic schools. The guidelines of Law 11,947 / 2009 establish, in addition to meeting the nutritional needs of students, the requirement to apply at least 30% of the resources to purchase food produced in the Family Agriculture field, promote Food and Nutrition Education and preparation of menus that respect local eating habits. From this perspective, the qualitative study is an evaluation of the influence of PNAE on eating habits in school communities in the city of Coruripe, Alagoas. In order to develop the research, we carried out a large bibliographical review, secondary data collection on official and primary sites with field research in two educational units located in rural communities of Coruripe. Family farmers, nutritionists, school cooks, dwellers, parents and students of the two schools were the subjects that constituted the sources of the primary data obtained through directed interviews and textual production activities. The results point to adjustments in food acquisition and school menus focused on the valorization of territorialities, social reproduction practices of the families of producers and local eating habits. However, we emphasize the need for actions aimed at the expansion or inclusion of new family farmers in the Program, debates on agroecological production and deepening of the issues related to the problems arising from the dominant productive system.